2020
DOI: 10.1371/journal.pone.0230755
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes seed germination under salinity and enhances the biosynthesis of steviol glycosides in Stevia rebaudiana Bertoni leaves

Abstract: Melatonin (MEL) can act as a plant growth regulator and biostimulator in stressful situations. Using MEL in seed pretreatment also affects the future growth of plants. Therefore, this research investigated the effects of MEL on seed germination and seedling growth under NaCl in in vitro conditions. The additional effects of MEL on the accumulation of steviol glycosides (SGs) and on the expression of appropriate genes were also studied. Five μM of MEL was the best concentration for seed germination, while 20 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…For example, a higher level of germination post‐heat stress was obtained with the 1000 µM MT treatment 48 . Moreover, exogenous melatonin promoted seed germination under salt stress in cotton, cucumber, and Stevia rebaudiana Bertoni 49‐51 . These studies show that MT may be involved in seed germination.…”
Section: Introductionmentioning
confidence: 72%
“…For example, a higher level of germination post‐heat stress was obtained with the 1000 µM MT treatment 48 . Moreover, exogenous melatonin promoted seed germination under salt stress in cotton, cucumber, and Stevia rebaudiana Bertoni 49‐51 . These studies show that MT may be involved in seed germination.…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, it was feasible to improve seed germination by using phytohormones, i.e., MT, in agricultural productions. Indeed, MT has been widely and effectively applied to alleviate the stress-induced delays of seed germination in various plants ( Posmyk et al, 2008 ; Zhang et al, 2013 , 2014 ; Hernández et al, 2015 ; Chen et al, 2020 ; Simlat et al, 2020 ). In this research, we found that the applications of exogenous MT significantly improved the germination rates ( Figures 1 , 2A,B and Supplementary Figures 3A,B ) and seedling performance ( Supplementary Figures 3C,D ), which were largely related to the recovery of water absorption ( Supplementary Figure 3D ) and membrane permeability ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous applications of melatonin ( N -acetyl-5-methoxytryptamine, MT) have been determined as an effective way to improve seed germination under various stress conditions ( Hernández et al, 2015 ; Xiao et al, 2019 ; Simlat et al, 2020 ). For example, exogenous MT enabled the promotion of seed germination under salinity ( Zhang et al, 2014 ) and water stress ( Zhang et al, 2013 ) in cucumber ( Cucumis sativus L.) while high levels of germination under post-salt and toxic copper ion stress conditions were also observed in cotton ( Gossypium hirsutum L.) ( Chen et al, 2020 ) and in red cabbage ( Posmyk et al, 2008 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest stevioside and rebaudioside A (Reb A) values were obtained from 5 and 20 µM MEL application of seeds, respectively. Steviol glycoside gene expression in young leaves varied according to MEL concentration (Simlat et al, 2020).…”
Section: Exogenous Application Of Melatonin At Germination Stage Unde...mentioning
confidence: 99%